The use and abuse of dogs on Scott's and Amundsen's South Pole expeditions - Murray, Carl (Polar Record, 2008)
In the century since Roald Amundsen and Robert F. Scott led the first and second expeditions to reach the South Pole, commentators have frequently passed judgement on the different means of transport that the two explorers employed. In hindsight, and since he ‘won,’ they have consistently praised Amundsen for using dogs exclusively and criticised Scott for not doing the same. Surprisingly, however, almost no attention has been given to the experience of Amundsen's dogs, whose extreme suffering seems to have vanished into a collective blind spot. Here, with the aim of restoring balance to one part of the vexed historiography of the two explorers, that record is set straight. Amundsen's troubled and contradictory attitude towards his animals is also explored and common misconceptions about Scott's views on the use of dogs for transport are confuted.
Publisher: Cambridge University Press
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie; sledehunder

Sledge dogs of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Reece, Alan (Polar Record, 1954)
Publisher: Cambridge University Press
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; sledehunder

Gjennem isbaksen : atten år med Roald Amundsen - Hanssen, Helmer (Aschehoug, 1941)
Keywords: Antarktis; Fram (skip); Maud; Roald Amundsen; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene; sledehunder; sydpolen

Voyages of a modern Viking - Hanssen, Helmer (George Routledge & Sons, 1936)
Keywords: Antarktis; Fram (skip); Maud; Roald Amundsen; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene; sledehunder; sydpolen

The Norwegian Expedition to the Antarctic (The Geographical Journal, 1933)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Hjalmar Riiser; Larsen; ekspedisjoner; oppdagelsesreiser; sledehunder